THE PECULIARITIES OF ND-FE-B BASED ALLOY CRUSHING IN ELECTROMAGNETIC FIELD - YU.M. VERNIGOROV; I.N. EGOROV; S.I. EGOROVA (Advanced Engineering Research, 2006)
The analysis of Nd-Fe-B based alloy crushing products grain size distribution was used to investigate the peculiarities of alloy crushing process in the impact mill at various electromagnetic field parameters. The correlation of constant and variable magnetic field induction and variable magnetic field induction gradient, providing the effective crushing and homogeneity of crushing product sizes was obtained.